2011
DOI: 10.1073/pnas.1109696108
|View full text |Cite
|
Sign up to set email alerts
|

Rumi functions as both a protein O -glucosyltransferase and a protein O -xylosyltransferase

Abstract: Mutations in rumi result in a temperature-sensitive loss of Notch signaling in Drosophila . Drosophila Rumi is a soluble, endoplasmic reticulum-retained protein with a CAP10 domain that functions as a protein O -glucosyltransferase. In human and mouse genomes, three potential Rumi homologues exist: one with a high degree of identity to Drosophila Rumi (52%), and two others with lower degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 36 publications
1
91
0
Order By: Relevance
“…2B). Using the radioactive assay, mN2 EGF16 was an excellent substrate for both Poglut and Poxylt activity of Poglut/Rumi, consistent with our prior mass spectral results (15). The FA9 N54S mutant showed similar Poglut activity compared with wild type but significantly higher Poxylt activity (Fig.…”
Section: Poglut/rumi Only Modifies Properly Folded Egf Repeats-supporting
confidence: 77%
See 2 more Smart Citations
“…2B). Using the radioactive assay, mN2 EGF16 was an excellent substrate for both Poglut and Poxylt activity of Poglut/Rumi, consistent with our prior mass spectral results (15). The FA9 N54S mutant showed similar Poglut activity compared with wild type but significantly higher Poxylt activity (Fig.…”
Section: Poglut/rumi Only Modifies Properly Folded Egf Repeats-supporting
confidence: 77%
“…EGF27 from mN1 (26) and EGF16 from mouse Notch2 (mN2) (14)). We also found an O-xylose modification at the O-glucose consensus site of EGF16 from mN2 and demonstrated that Poglut/Rumi utilizes UDP-xylose as well as UDP-glucose as donor substrate (15). The presence of a di-serine motif within the O-glucose consensus sequence, as found in mN2 EGF16, appears to enhance use of UDP-xylose by Poglut/Rumi (15).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…At least five different glycan modifications have been found on the Notch EGF-like repeats: N-linked glycan modifications (8) and four O-linked glycan modifications: O-fucose (9 -11), O-glucose (12,13), O-GlcNAc (14), and O-GalNAc (15). A potential O-xylosylation of the EGF-like repeats has also been observed in vitro (16). The individual modifications have been analyzed to determine their specific functions and generate a model for how glycosylation regulates receptor functions (8 -15).…”
mentioning
confidence: 94%
“…The plasmids used for secretion assays were pSecTag2c-Notch1 EGF(1-36)-Myc-His 6 (44), pcDNA4-POGLUT1-Myc-His 6 (45), and pSecTag2c-POFUT1-Myc-His 6 (7). A plasmid encoding human IgG (3) was used as secretion control.…”
Section: Secretion Assays With Notch1 Extracellular Domainmentioning
confidence: 99%